2023
DOI: 10.3390/ijms24076813
|View full text |Cite
|
Sign up to set email alerts
|

Nisin S, a Novel Nisin Variant Produced by Ligilactobacillus salivarius P1CEA3

Abstract: Recently, the food industry and the animal farming field have been working on different strategies to reduce the use of antibiotics in animal production. The use of probiotic producers of antimicrobial peptides (bacteriocins) is considered to be a potential solution to control bacterial infections and to reduce the use of antibiotics in animal production. In this study, Ligilactobacillus salivarius P1CEA3, isolated from the gastrointestinal tract (GIT) of pigs, was selected for its antagonistic activity agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The assembled L. salivarius P1CEA3 genome, evaluated with the BAGEL v.4.0 and antiSMASH servers, indicated the existence of two distinct bacteriocin gene clusters in pMP1CEA3, one encoding the class II bacteriocins salivaricin B (SalB) and Abp118 (Abp118α and Abp118β), previously characterized in L. salivarius M6 and L. salivarius UCC118, respectively [ 58 , 59 ], and a second gene cluster encoding the lantibiotic nisin S [ 20 ]. The arrangement of genes within the nisin S gene cluster of pMP1CEA3 was nssABTCRKFEG , lacking the genes encoding a specific peptidase and an immunity protein, as compared to the nisin A gene cluster of Lactococcus lactis [ 20 ]. Previous results also demonstrated that although the abp118 structural genes of L. salivarius P1CEA3 were functional, deletions and mutations in genes related to its transport ( abpT and abpD ) and regulation ( abpK ) were preventing the synthesis and secretion of Abp118.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The assembled L. salivarius P1CEA3 genome, evaluated with the BAGEL v.4.0 and antiSMASH servers, indicated the existence of two distinct bacteriocin gene clusters in pMP1CEA3, one encoding the class II bacteriocins salivaricin B (SalB) and Abp118 (Abp118α and Abp118β), previously characterized in L. salivarius M6 and L. salivarius UCC118, respectively [ 58 , 59 ], and a second gene cluster encoding the lantibiotic nisin S [ 20 ]. The arrangement of genes within the nisin S gene cluster of pMP1CEA3 was nssABTCRKFEG , lacking the genes encoding a specific peptidase and an immunity protein, as compared to the nisin A gene cluster of Lactococcus lactis [ 20 ]. Previous results also demonstrated that although the abp118 structural genes of L. salivarius P1CEA3 were functional, deletions and mutations in genes related to its transport ( abpT and abpD ) and regulation ( abpK ) were preventing the synthesis and secretion of Abp118.…”
Section: Resultsmentioning
confidence: 99%
“…Ligilactobacillus salivarius P1CEA3 was isolated from the GIT of slaughtered pigs as previously described [ 20 ]. L. salivarius P1CEA3 was grown overnight at 37 °C in tryptic soy broth (TSB) (Oxoid Ltd., Basingstoke, UK) under anaerobic conditions using anaerobic jars with an AnaeroGen 3.5 l pack (Oxoid).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, how nisin and nisin-like lantibiotics might impact the human gut microbiome has not been elucidated, nor has the presence of nisin-like compounds in the human gut microbiome been investigated in detail. The recent discovery of blauticin and nisin analogs clearly indicates that nisin-like molecules are encoded in the human microbiome, ,,, with other analogs detected in the microbiome of other mammals. , To first explore the biosynthetic potential of the gut microbiome for lantibiotic production, we systematically performed bioinformatic mining with RODEO for nisin-like lantibiotics derived from gut bacterial genomes. Subsequent filtering, multiple sequence alignment, and manual curation discovered six gut-derived nisin-like lantibiotics, four of which were not reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, culture-based techniques have been used to discover natural variants of nisin and other new bacteriocins ( Figure 1 ). 11 However, these techniques have limitations, which include laborious processes, low bacteriocin production under standard laboratory culturing conditions, and an increasing probability of rediscovering already known bacteriocins. To overcome these challenges, genome-guided methods that detect biosynthetic gene clusters (BGCs) that may encode novel nisin variants can be applied due to their numerous advantages.…”
Section: Introductionmentioning
confidence: 99%